Spanish Civil War: The recovery and identification of combatants. (March 2021) - Herrasti, Lourdes; Márquez-Grant, Nicholas; Etxeberria, Francisco
Abstract: In the context of exhumations of individuals who died during the Spanish Civil War (1936–1939), since the year 2000, over 780 mass graves have been excavated using archaeological methodology and following forensic protocols. Most of the recovered more than 9600 bodies have tended to be from the Republican civil population, the majority having been executed extrajudicially. However, a number of exhumations relate to the remains of soldiers who died in combat. In fact, approximately 100 individual or mass graves have been investigated and exhumed, containing the remains of combatants. These burials tend to be in the same location where they fell, usually in the front line, or close to the field hospitals where they went after being wounded initially. During the recovery of the human remains, a number of artefacts related to the uniform as well as personal effects have been found. An interdisciplinary approach from archaeology, anthropology, genetics, history and other disciplines has enabled the identification of some of these combatants. The aim of this paper is to present the data obtained from these combatants and highlight the work undertaken in Spain, and the efforts by scientists to exhume, identify and return the remains to relatives where possible.